Pengenalan Modalitas Fisioterapi Untuk Penanganan Hipertensi Pada Lansia Di Desa Gatak - Wijianto Wijianto; Salma Hira Ayu Setyara; Azizah Rahma Sarita; Dwi Mutiara (Jurnal Pengabdian Masyarakat, 2023)
Hypertension is a condition in which abnormally increased blood pressure in the arterial vessels secra continuously for more than one period, according to the WHO, a person is said to have hypertension when the blood pressure reaches >160/95 mmHg and is considered normal. Hypertension can be influenced by lifestyle and diet. There are many ways to cope with hypertension such as a healthy lifestyle and routine health checks to control blood pressure. Another way to deal with hypertension in the elderly is to use physiotherapy modalities, including breathing exercises to help lower blood pressure and fast walking exertions that work through reduced peripheral resistance.